Northern Ireland Peace Talks (1993–1998): Factors of Success - A. A. Nosach (Международная аналитика, 2018)
The article examines the final phase of Northern Ireland peace negotiations (1993–1998), which resulted in the Good Friday Agreement, a document that established the current constitutional status of the country. After a brief overview of the history of the conflict, the stances of the parties concerned are described, an outline of the negotiation process is traced and an analysis of the resulting agreement is given. The author concludes that the key to the success of the talks consisted in the following factors: due consideration of the opinions of those political parties and paramilitaries that were involved in the conflict; proper prioritization in regard to the goals of the negotiations; the principles of equality of the parties and democratic consent of the Irish people as the foundation for the peace process.